Contesting power, reclaiming identity: the political identity formation of the Economic Freedom Fighters in post-colonial South Africa - France Khutso Lavhelani Kgobe; Koketso Sophia Letsoalo (Annales Scientia Politica)
The establishment of the Economic Freedom Fighters (EFF) party has had a significant impact on South African politics since its launch in 2013. Following the 2014 general election, the EFF became the third-largest party, alongside the African National Congress and the Democratic Alliance, in the National Assembly. In the 2016 local elections, the party captured 8.2% of the national vote. This study seeks to explore the EFF’s identity formation in post-colonial South African socio-political landscape. Drawing theoretically from the discourse of post-colonialism, the study analysis the EFF’s political identity, the complex intersection of historical grievance, socio-economic transformation and the how colonial and apartheid legacies has influenced the party’s identity and its uniform and rhetoric approach to politics through the party’s manifestos, media texts and the key speeches. The reveals how the EFF’s identifies itself with the marginalised population seeking to reclaim their identity and agency in the political landscape by sparking debates around the country’s political institutions 30 years into the democratic system.